141k views
12 votes
Can someone help and explain it step by step, please!!

Can someone help and explain it step by step, please!!-example-1
User Yosriz
by
4.3k points

1 Answer

7 votes

9514 1404 393

Answer:

(x, y) = {(-32/17, 49/17), (-2, 1)}

Explanation:

I find a graphing calculator to be quite helpful in finding the solutions.

(x, y) = {(-1.882, 2.882), (-2, 1)}

__

For this sort of system of equations, substitution works nicely as a solution method.

The first equation tells us ...

y = 1 - x

Using that in the second equation, we get ...

16x² +(1 -x)² = 65

16x² +1 -2x +x² = 65 . . . . . eliminate parentheses

17x² -2x -64 = 0 . . . . . . . . collect terms, subtract 65

(x -2)(17x +32) = 0 . . . . . . . factor

Solutions are the values of x that make the factors zero: x = 2, x = -32/17.

The corresponding y-values are ...

for x=2, y = 1-2 = -1

for x=-32/17, y = 1-(-32/17) = 49/17

The solutions are ...

(x, y) = (2, -1) or (-32/17, 49/17)

Can someone help and explain it step by step, please!!-example-1
User DontCareBear
by
5.3k points